CYP21A2 Mutations in Women with Polycystic Ovary Syndrome (PCOS) - Settas, N.; Dracopoulou-Vabouli, M.; Dastamani, A.; Katsikis, I.; Chrousos, G.; Panidis, D.; Dacou-Voutetakis, C. (Hormone and Metabolic Research, 2013)
The question of the contribution of CYP21A2 heterozygosity to the development of polycystic ovary syndrome (PCOS) has repeatedly been raised in the literature. The available data, however, do not offer a satisfactory answer. The discrepancy must be attributed, primarily, to the small number of subjects in the various studies, the type of selected phenotype, and the number of searched mutations. The aim of the study was to define the contribution of CYP21A2 heterozygous mutations to the pathogenesis of PCOS. We searched for 14 molecular defects of the CYP21A2 gene in 197 PCOS women, employing allele specific PCR. Androgen levels were determined at baseline by appropriate methodology in the follicular phase. PCOS women with 17-hydroxyprogesterone (17OHP) basal values >2 ng/ml and/or post-ACTH >10 ng/ml were excluded. Appropriate controls were included. The frequency of the CYP21A2 heterozygous mutations in PCOS women and in controls was 7.6% and 5.9%, respectively [p-value (PCOS vs. controls): 0.663]. Homozygosity for CYP21A2 gene defects was not detected. In conclusion, the contribution of CYP21A2 heterozygous mutations to the pathogenesis of PCOS is not substantiated by our data. Moreover, 17-hydroxyprogesterone values of < 10 ng/ml post-ACTH exclude homozygosity of CYP21A2 mutations.
Keywords: CYP21A2 gene; PCOS; hyperandrogenemia; CAH; molecular defects